Karakterisasi Bahan Kampas Rem Sepeda Motor Dari Komposit Serbuk Kayu Jati - Yudhanto, Ferriawan; Dhewanto, Santo Ajie; Yakti, Suluh Widya (Universitas Muhammadiyah Yogyakarta, 2019)
Commonly the prime material for brake pad of the commercial motorcycle using asbestos, these materials cause a disease like as cancer of respiration if the abrasive particles were sniffed. The SKJ (Serbuk Kayu Jati) brake pad is alternative to replacement the asbestos brake pads. The mechanical test includes a wear test, hardeness test, friction coefficient test, and heat resistant test. The hot press process for SKJ as main material of brake pad based by variation of temperature there are 160ºC, 170ºC, and 180ºC. The optimum test result of SKJ brake pads is a variation of 180ºC with wear test result is 3,36 x 10-7 mm2/kg, the hardeness result is 25,1 BHN, the friction coefficient test is 0,59 and not damaged on the heat resistant test with a temperature of 300ºC during an hour.